Perception-based Indicator for Sustainability of Shrimp Culture in the Less Favorable Areas at Southern Coast of Yogyakarta - Suadi Suadi; Hery Saksono; Bambang Triyatmo (Jurnal Perikanan Universitas Gadjah Mada, 2019)
Shrimp farming has been introduced since the mid-1980s at the southern coast of Daerah Istimewa Yogyakarta (DIY). However, the industry was not well growing in the initial stage. The new shrimp development project also promoted in the early of 2000s, particularly in Jangkaran Village, Subdistrict of Temon, Kulon Progo District and Poncosari Village, Subdistrict of Srandakan, Bantul District, but many of shrimp farms fail because of shrimp diseases, lack of capital to recover and shrimp farming experiences. Recently, the shrimp culture industry experienced rapid expansion along the coast of the two districts. This study aimed to determine the profile and growing of shrimp farming at the southern coast of DIY and to identify the technical aspects, social, and economic indicators of sustainable shrimp culture in the less favorable areas. To identify the sustainability of current shrimp culture, the study develop four indicators consist of technical indicators (6 sub-indicators), economic indicators (9 sub-indicators), social indicators (7 sub-indicators), and environmental indicators (8 sub-indicator). The study was conducted during March to October 2014 by using a combination of literature study and survey at two selected villages: Jangkaran and Poncosari Villages. The total 82 respondents were interviewed; consist of shrimp farmers, coastal communities, community leaders, and local government. The study showed that the rapid growing of shrimp farming were caused by several factors, among others: (1) the existence of technological innovation in shrimp farming in the sandy soil areas, particularly the lower cost in the pond investment and the more easier of seawater collecting; (2) high price and market opportunities of the commodity; and (3) changes in the physical environment due to the threat of coastal erosion which damage the fisher livelihood, thus demanding adaptation strategies. Shrimp farmer in average managed 2,138 m2 and implemented intensive to super intensive cultivation technology, with an average stocking density of 144 shrimp/m2. Production per year in average reaches 25.9 ton/ha and generating revenue of IDR286.544.232 per year. The total cost of production is estimated at IDR210.590.175 per year, and generated a net profit of IDR75.954.057 per year. The perception based indicator of sustainability showed the environmental related issues were in average have a low value. Thus, environmental regulation of aquaculture is an important aspect to be considered in promoting sustainable development of shrimp farming at the southern coast of the province.